Pengembangan Kognitif Melalui Penggunaan Game Edukasi Digital Untuk Anak Usia 5 - 6 Tahun Di Tk Riverside Tahun Pelajaran 2022/2023 - Sri - Lestari; Sugito - Muzaqi; Andini dwi Arumsari (Pedagogi : Jurnal Anak Usia Dini dan Pendidikan Anak Usia Dini, 2024)
Cognitive Development Through the Use of Digital Educational Games for Children Aged 5-6 Years at Riverside Kindergarten 2022/2023 Academic YearCognitive of children aged 5-6 years in Kindergarten Riverside Surabaya is still very low. This is because learning at Riverside Kindergarten is still not attractive to students. Therefore it is necessary to change the strategy in learning for children's cognitive development. Educational games excel in several aspects compared to conventional learning designs. One of its advantages is the existence of animation which can improve memory, so it can store learning material for quite a long time.This research aims at cognitive development through the use of digital educational games. The subjects of this study were group B, which consisted of 19 children and 1 group B teacher at Riverside Kindergarten. This research method uses the CAR method (classroom action research) with the model approach used by Kemmis and Mc. Taggart. Data collection techniques are carried out through observation and documentation. This research procedure consists of 4 stages, namely planning, implementation, observation, and reflection.Digital educational game media can be used to support teachers when delivering learning material. As well as really helping children in a fun learning process. This digital educational game can be a learning medium for children aged 5-6 years to get to know the ABCD pattern, recognize various kinds of vowel and consonant symbols, and present objects in written form. Learning to use digital educational games is able to develop the cognitive abilities of children aged 5-6 years at the Riverside Kindergarten in Surabaya.Keywords: Cognitive, Digital Educational Game